At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

f(1) = -6

f(2) = -4

f(n) = f(n − 2) + f(n − 1)

f(3) =


Sagot :

Answer:

-10

Step-by-step explanation:

f(n)= f(n-2)+f(n-1)

• Put n = 3

=> f(3) = f(3-2) + f(3-2)

=> f(3) = f(1) + f(2)

=> f(3) = -6 + -4

=> f(3) = -10

Answer:

it in a file here

Step-by-step explanation:

xycba.com/file